2017
DOI: 10.1007/s12328-017-0785-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful chemotherapy with modified FOLFIRINOX for pancreatic acinar cell carcinoma

Abstract: Abdominal ultrasonography revealed a pancreatic mass in a 67-year-old man with diabetes mellitus. Endoscopic ultrasound-guided fine needle aspiration led to the histological diagnosis of acinar cell carcinoma. The clinical stage was determined to be IVb based on findings of multiple metastatic lesions in the liver and lymph nodes, as well as splenic vein infiltration. Because the patient was not a surgical candidate, he underwent chemotherapy with modified FOLFIRINOX. In the absence of any severe adverse event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…As in PDAC, surgical resection should be performed in PACC with a goal of achieving R0 margins [ 12 ]. For metastatic PACC, the chemotherapy protocol of PDAC has been used, which includes gemcitabine, 5-FU, oxaliplatin, CPT-11, and S-1, or their combinations [ 14 16 ]. A systematic review by Glazer et al demonstrated that the disease control rate of chemotherapy was 55% and median survival time in metastatic PACC after chemotherapy was 17 months [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in PDAC, surgical resection should be performed in PACC with a goal of achieving R0 margins [ 12 ]. For metastatic PACC, the chemotherapy protocol of PDAC has been used, which includes gemcitabine, 5-FU, oxaliplatin, CPT-11, and S-1, or their combinations [ 14 16 ]. A systematic review by Glazer et al demonstrated that the disease control rate of chemotherapy was 55% and median survival time in metastatic PACC after chemotherapy was 17 months [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acinar cell carcinoma (ACC) represents approximately 1% of all pancreatic neoplasms, which primarily occur in late adulthood [ 8 , 9 ], with a male to female ratio of 3.6:1 [ 10 ]. Most patients with pancreatic ACC have no specific symptoms, and the non-specific clinical symptoms include weight loss (52%), abdominal pain (32%), nausea and vomiting (20%), melena (12%), weakness, anorexia or diarrhea (8%) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yoo et al [ 18 ] confirmed that oxaliplatin-based chemotherapy had improved activity against pancreatic ACC as compared to gemcitabine. Hashimoto et al [ 9 ] suggested that modified FOLFIRINOX was safe and effective in the treatment of pancreatic ACC.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, due to the local expansion and the good condition of the patient, we proposed modified FOLFIRINOX, which is the best available adjuvant option, analogous with the ductal histology. 11 In addition, Hashimoto et al (2017) suggested that modified FOLFIRINOX was safe and effective in the treatment of pancreatic ACC. 12 Also in treating the advanced disease, we adopted the chemotherapy regimens approved for ductal adenocarcinoma, which included gemcitabine plus nab-paclitaxel in the first-line, and liposomal irinotecan plus 5-fluorouracil in the refractory setting.…”
Section: A B Cmentioning
confidence: 99%
“…11 In addition, Hashimoto et al (2017) suggested that modified FOLFIRINOX was safe and effective in the treatment of pancreatic ACC. 12 Also in treating the advanced disease, we adopted the chemotherapy regimens approved for ductal adenocarcinoma, which included gemcitabine plus nab-paclitaxel in the first-line, and liposomal irinotecan plus 5-fluorouracil in the refractory setting. 13,14 Our patient experienced a good response with gemcitabine plus nab-paclitaxel, which gave him the opportunity to be considered for a maximal approach, including liver surgery.…”
Section: A B Cmentioning
confidence: 99%